Nutritional status and physical activity levels of adolescents in public and private schools - Arias-Silva, María V; Pedreros-Lemuz, Valentina; Rodríguez-Perdomo, Angie L; González-Lozano, Raúl A; Ramos-Castaneda, Jorge A (Revista Cuidarte, 2024)
Highlights• The prevalence of overweight and obesity was high in both educational institutions.• The overall level of physical activity in the adolescents was low.• Public school students were more physically inactive compared to private school students.• Tenth and eleventh graders are more physically inactive than ninth graders.Introduction: Obesity and physical inactivity in adolescents are associated with some diseases, and poor academic performance. Studies have reported differences in the level of physical activity according to the type of school.  Objective: To compare the prevalence of obesity and physical inactivity in adolescents in a public and a private school. Materials and Methods: A cross-sectional study was conducted among adolescents attending a public school and a private school. Ninth, tenth, and eleventh-grade students between 14 and 17 years were included. Physical activity level was assessed using the Physical Activity Questionnaire for Adolescents, and nutritional status using body mass index for age. Results: Information was collected from 343 students, of whom 55.10% (n=189) were from a public school. The 28.28% were overweight. The overall level of physical activity in adolescents was low (mean= 1.97 95% CI 1.92 – 2.01). It was found that public school students were more inactive adjusted (PR= 1.40; 95% CI 1.03 - 1.92) compared to private school students.    Discussion:    Adolescents do not achieve optimal levels of frequency and duration of physical activity, highlighting the need for educational programs and attractive interventions to promote physical activity. Conclusion: Adolescent students have low levels of physical activity, with more inactive students in the public school compared to the private school. The prevalence of overweight was high in both schools.How to cite this article: Arias-Silva María V, Pedreros-Lemuz Valentina, Rodríguez-Perdomo Angie L, González-Lozano Raúl A, Ramos-Castaneda Jorge A. Nutritional status and physical activity levels of adolescent in public and private schools. Revista Cuidarte. 2024;15(3):e3942.  https://doi.org/10.15649/cuidarte.3942
Keywords: Exercise; Sedentary Behavior; Adolescent; Obesity; Nutritional Status